2018
DOI: 10.7554/elife.41076
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetics enables real-time spatiotemporal control over spiral wave dynamics in an excitable cardiac system

Abstract: Propagation of non-linear waves is key to the functioning of diverse biological systems. Such waves can organize into spirals, rotating around a core, whose properties determine the overall wave dynamics. Theoretically, manipulation of a spiral wave core should lead to full spatiotemporal control over its dynamics. However, this theory lacks supportive evidence (even at a conceptual level), making it thus a long-standing hypothesis. Here, we propose a new phenomenological concept that involves artificially dra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 52 publications
0
49
0
1
Order By: Relevance
“…Our results confirmed that the typical basin of attraction of a circular inhomogeneity, for both conduction-type and light-induced cases, is circular, provided the spiral was exposed to the inhomogeneity for a reasonably long time (>3 s) (see figure 3. At short timescales, while the basin of attraction for a conduction-type inhomogeneity remained circular, with lower average probability of attraction at shorter observation times, the basin of attraction of a light-induced inhomogeneity developped a bias, as in figure 3 of Majumder et al [8] indicating that brief light pulses could be used for directed attraction-based movement, as is required for AAD.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Our results confirmed that the typical basin of attraction of a circular inhomogeneity, for both conduction-type and light-induced cases, is circular, provided the spiral was exposed to the inhomogeneity for a reasonably long time (>3 s) (see figure 3. At short timescales, while the basin of attraction for a conduction-type inhomogeneity remained circular, with lower average probability of attraction at shorter observation times, the basin of attraction of a light-induced inhomogeneity developped a bias, as in figure 3 of Majumder et al [8] indicating that brief light pulses could be used for directed attraction-based movement, as is required for AAD.…”
Section: Resultsmentioning
confidence: 94%
“…To this end, we first produced a stationary rotating vortex, pinned to a circular conductiontype inhomogeneity, in a simulated monolayer of neonatal rat cardiac atrial cells. Next, we created a circular light-induced inhomogeneity, close to the location of the anchored vortex, by applying a light spot to the in silico monolayer, as described in Majumder et al [8]. We observed unpinning of the anchored vortex from the conduction-type inhomogeneity, followed by its re-attachment to the light-induced inhomogeneity.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations